Web Resources for Microbial Data - Qinglan Sun; Li Liu; Linhuan Wu; Wei Li; Quanhe Liu; Jianyuan Zhang; Di Liu; Juncai Ma (Genomics, Proteomics & Bioinformatics, 2015)
There are multitudes of web resources that are quite useful for the microbial scientific research community. Here, we provide a brief introduction on some of the most notable microbial web resources and an evaluation of them based upon our own user experience.